Integrating bioagent with botanical and fungicide in different modes of application for better management of web blight and mungbean (Vigna radiuta) yield - DUBEY, S C (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2002-03 at New Delhi to study the efficacy of Trichodernla viride (IARIP-21, Ponganzia giabra Vent cake and leaf extract and carboxin in different combinations and modes of application in field trials for the management of web blight (Rhizoctonia solani Kiihn). The resulting yield of mungbean (Vigna radiata (L.) Wilczek) was measured. Fifty-four combinations of different treatments were applied through soil, seed and foliar spray. Integration of soil application of P. glabra cake (200 kgha), seed treatment with T. viride (2 gkg seed) + carboxin (1 g/ kg seed) + Rhizobiltn s p (25 g kgse ed) and foliar spray of P. glabra leaf extract (10%) suppressed disease severity to a significant extant (92.7 %). This treatment also increased seed germination (32.4%), improved plant vigour and enhanced production (49.2%). The same combination excluding carboxin was also effective and could be an option for organic production of mungbean. The integration of any two modes of applications of treatments was superior to any single mode of application.